2018
DOI: 10.1002/bio.3454
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence‐based cytotoxicity assay for simultaneous evaluation of cell viability and membrane damage in human hepatoma HepG2 cells

Abstract: We have developed a bioluminescence-based non-destructive cytotoxicity assay in which cell viability and membrane damage are simultaneously evaluated using Emerald luciferase (ELuc) and endoplasmic reticulum (ER)-targeted copepod luciferase (GLuc-KDEL), respectively, by using multi-integrase mouse artificial chromosome (MI-MAC) vector. We have demonstrated that the time-dependent concentration response curves of ELuc luminescence intensity and WST-1 assay, and GLuc-KDEL luminescence intensity and lactate dehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…First, to examine the appropriateness of cytotoxicity assessment by bioluminescence measurement, we conducted non-destructive bioluminescence measurement and the WST-1 assay in parallel using CYP-non-expressing luminescent HepG2 cells (ELuc-HepG2 cells) and CYP-expressing luminescent HepG2 cells (CYPs-ELuc-HepG2 cells). We confirmed that the decrease of bioluminescence intensity well correlated with the increase of cytotoxicity, as reported previously [19][20][21]. Furthermore, we obtained similar concentration-response curves for SDS-(non-selective toxicant) or dimethyl fumarate-(CYP-independent toxicant) treated ELuc-HepG2 and CYPs-ELuc-HepG2 cells, respectively (Figure 2), indicating that the sensitivity of the two cell lines to CYP-independent cytotoxicity is almost the same.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…First, to examine the appropriateness of cytotoxicity assessment by bioluminescence measurement, we conducted non-destructive bioluminescence measurement and the WST-1 assay in parallel using CYP-non-expressing luminescent HepG2 cells (ELuc-HepG2 cells) and CYP-expressing luminescent HepG2 cells (CYPs-ELuc-HepG2 cells). We confirmed that the decrease of bioluminescence intensity well correlated with the increase of cytotoxicity, as reported previously [19][20][21]. Furthermore, we obtained similar concentration-response curves for SDS-(non-selective toxicant) or dimethyl fumarate-(CYP-independent toxicant) treated ELuc-HepG2 and CYPs-ELuc-HepG2 cells, respectively (Figure 2), indicating that the sensitivity of the two cell lines to CYP-independent cytotoxicity is almost the same.…”
Section: Discussionsupporting
confidence: 90%
“…Next, to verify the sensitivity of the two cell lines to toxicants whose toxicity does not depend on CYP metabolism, we conducted non-destructive bioluminescence measurement and water-soluble tetrazolium-1 (WST-1) assay in parallel ( Figure 2). After ELuc-HepG2 and CYPs-ELuc-HepG2 cells were treated with toxicant, the cells were incubated in the presence of D-luciferin, a bioluminescent substrate for ELuc, for three days and bioluminescence intensity was measured non-destructively thereafter, as reported previously [20,21]. Then, the WST-1 assay was performed using the same cells.…”
Section: Comparison Of Sensitivity Of Eluc-hepg2 and Cyps-eluc Hepg2 mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the level of formazan formation is directly proportional to the amount of released LDH in the medium. This assay is a better indicator of necrotic cell death and cytotoxicity [ 146 , 148 ]. Recent studies in our laboratory show that some sulfonamide inhibitors affect cell growth without inducing cytotoxicity and vice versa (Mboge et al submitted).…”
Section: Biochemical and Cell Based Assays To Decipher The Role Of Camentioning
confidence: 99%